Intimate Relationship Dynamics and Changing Desire for Pregnancy Among Young Women. Issue 3 (13th September 2019) - Barber, Jennifer S.; Miller, Warren; Kusunoki, Yasamin; Hayford, Sarah R.; Guzzo, Karen Benjamin
Abstract : CONTEXT: Although substantial research has focused on unintended pregnancy among young women, less is known about the circumstances under which pregnancy is desired. Whether a young woman's pregnancy desire changes across her different relationships, or over time within a relationship, has not been directly assessed. METHODS: Data on intimate relationships and pregnancy desire were assessed weekly for 895 women aged 18–22 who participated in the Relationship Dynamics and Social Life study in a county in Michigan (2008–2012). Within‐between logistic regression models were used to examine within‐cluster and between‐cluster differences—comparisons of a woman's pregnancy desire within a relationship over time as well as across a woman's different relationships. RESULTS: Young women were more likely to desire pregnancy if they were in any relationship more intimate and committed than a casual relationship (odds ratios, 1.6–9.2); the odds of desiring pregnancy were also higher in long‐term relationships rather than in short‐term ones (2.1). In general, pregnancy desire increased over time as a relationship endured and became more serious. The odds of desiring pregnancy were lower among women with less educated, rather than equally educated, partners (0.7), while the odds were higher in nonmonogamous or violent relationships than in monogamous or nonviolent relationships (1.6 and 1.9, respectively). CONCLUSIONS: Young women's pregnancy desire changes depending on their intimate relationship context, across the range of relationships they experience during the transition to adulthood.